Default and naive diversification heuristics in annuity choice. (February 2017) - Bateman, Hazel; Eckert, Christine; Iskhakov, Fedor; Louviere, Jordan; Satchell, Stephen; Thorp, Susan
Retirement income stream products are difficult for consumers to choose because of their high perceived risk, irreversibility, high expenditure, little opportunity for social learning and distant consequences. Prior literature is unclear about consumers' use of heuristics in decumulation decisions or whether sociodemographics can help identify vulnerable consumers. In the context of Australia's retirement income arrangements, we examine choices of life annuities and phased withdrawal products, and identify use of default options and the diversification (1/ n or 50:50) heuristic using a novel finite mixture modelling approach. The innovative feature of this approach is that it captures the very specific allocation pattern associated with choices based on deterministic decision rules, namely pronounced spikes at the locations of the particular heuristics with little mass in their surroundings. We show that more than 30% of decumulation choices rely on these two heuristics, and that cognitive and product knowledge limitations contribute to using such heuristics. The results have implications for public policy on decumulation of retirement savings, regulation of product disclosures and providers of annuity and phased withdrawal products. More generally, our model has the potential to provide better understanding of the use of heuristics in consumer decisions.